Disclosing Adult Wrongdoing: Maltreated and Non-Maltreated Children’s Expectations and Preferences - Malloy, Lindsay C. (2014)
Little is known about the process by which children disclose adult wrongdoing, a topic of considerable debate and controversy. In the present study, we investigated children’s evaluations of disclosing adult wrongdoing by focusing on children’s preferences for particular disclosure recipients and perceptions of the consequences of disclosure in hypothetical vignettes. We tested whether children thought disclosure recipients would believe a story child as a truth-teller and what actions the recipients would take against the “instigator” who committed the transgression. Maltreated and non-maltreated 4- to 9-year-olds (N = 235) responded to questions about vignettes that described a parent’s or stranger’s transgression. Older children preferred caregiver over police officer recipients when disclosing a parent’s, but not a stranger’s, transgression. Maltreated children’s preference for caregiver over police recipients developed more gradually than that of non-maltreated children. Older children expected disclosure recipients to be more skeptical of the story child’s account, and older children and maltreated children expected disclosure recipients to intervene formally less often when a parent rather than stranger was the instigator. Results contribute to understanding vulnerable children’s development and highlight the developmental, experiential, and socio-contextual factors underlying children’s disclosure patterns.